Anthropogenic pollution is widespread in Great Bowerbird bowers in northern Australia - Jennifer L. Lavers; Andrew L. Fidler; Hayley Charlton-Howard (Microplastics and Nanoplastics)
Abstract While the occurrence of anthropogenic pollution in bowerbird bowers has been well-known and documented for many years, there are limited studies detailing the scale of this occurrence, and even fewer discussing why bowerbirds utilise synthetic objects as bower decorations, and the potential impacts of using these items. Here, we examine the presence of various types of pollution, such as plastics, glass, and metal, in Juwe/Jurerrk, or Great Bowerbird (Chlamydera nuchalis) bowers (n = 17) across rural and remote northern Australia. Using a novel 3D scan technology to capture complete imagery of bower sites, we documented anthropogenic items (n = 2911) in all bowers; hard plastics were the most commonly found item (64.8%, n = 1887), with many pieces still intact and recognisable (e.g., bottle caps, clothes pegs, and tile spacers). In line with the species’ decoration colour preferences, the majority of items were white (70.7%), grey (16.7%), or green (10.3%). While the presence of anthropogenic items may increase the number of available ‘desirable’ decorations and improve mating success, they could pose an entanglement risk, cause mortality, and leach micro/nano-plastics and associated pollutants into the wider bower sites. This detailed record of the prevalence of anthropogenic pollution in bowers, including sites located within a National Park, provides a much-needed baseline for future research, allowing bowerbirds to become sentinels for their terrestrial ecosystems. Graphical Abstract